Forecasting chicken meat and egg in indonesia using ARIMA and SARIMA - M D Wisodewo; H A Rosyid; A R Taufani (Jurnal Informatika, 2022)
Abstract. Chicken meat and eggs are part of the main commodities in Indonesia. Indonesian people's consumption of chicken meat per capita per year continues to increase. Indonesian government is trying to lure investments to help fund these growing needs. However, inflation has never been positively affected investments. Furthermore, the price of chicken meat and eggs in Indonesia are vulnerable to such a fluctuation. This price hike causes losses to society, due to higher costs, and to the country: inflation affects the future of investment. So, if ones can forecast both commodities, could help decision makers optimizing their policies. This research forecasts the price of chicken meat and egg using the ARIMA and SARIMA methods. Price forecasting is done on chicken meat and egg because they are interrelated, as seen from the Pearson Correlation Test of 0.92 in the datasets and 0.87 in the forecasting results. The selection of the best model is based on the smallest MSE, MAE, and MAPE. The best chicken meat price forecasting results using the ARIMA(3, 1, 2) with MAPE value of 2.31%, while the best chicken egg price forecasting results is the SARIMA[(2, 1, 1)(2, 0, 2, 0), n] with MAPE value of 3.44%.